Antarcticella: a Paleogene typical foraminiferal genus from southernmost South America - Malumián, N. (2010)
The Patagonian and Fuegian regions conform a wide latitudinal and chronostratigraphical study area, where the abundant calcareous benthic foraminifera endemic to the Austral high and high-mid latitudes, have a partially or totally tuberculate surface. Among them, is the extinct Antarcticella, a small globular genus initially regarded as planktonic. The oldest species, A. pauciloculata (Jenkins), is widespread in the Danian from Patagonia, Antarctica, and New Zealand; the subsequent A. cecionii (Cañón and Ernst) is constrained to the Fuegian early and early middle Eocene; there is no record of Antarcticella from the mid middle Eocene, partially due to a sedimentary gap.